Risk Factors for Low Back Pain Among Rubber Factory Workers - Willia Novita Eka Rini; Budi Aswin; Fajrina Hidayati (Formosa Journal of Multidisciplinary Research, 2023)
Low back pain (LBP) significantly impacts Indonesian workers, including those in Jambi's rubber processing factories. This study, involving 102 respondents, used a cross-sectional design to identify LBP-associated factors. Statistical analysis found significant correlations: age (p-value 0.000, PR 1.83), years of service (p-value 0.000, PR 3.50), workload (p-value 0.000, PR 6.00), work attitude (p-value 0.000, PR 0.06), BMI (p-value 0.005, PR 1.20), and smoking (p-value 0.000, PR 2.42) with LBP complaints. Medical history had no significant association (p-value 0.351, PR 1.13). LBP complaints in rubber factory workers may be triggered by factors such as advancing age, length of service, heavy workloads, suboptimal work attitudes, abnormal BMI, and smoking habits.